Renal Epithelioid Angiomyolipoma with Epithelial Cysts Mimicking Cystic Renal Cell Carcinoma: A Case Report of Combination of Two Rare Entities - Sang Hoon Lee; Jeong Sub Lee; Jeong Jae Kim; Su Yeon Ko; Kyung Ryeol Lee; Im Kyung Hwang; Chang Lim Hyun (대한영상의학회지, 2022)
Renal angiomyolipomas (AMLs) are typically solid tumors, but there have been few reports of a rare cystic variant of AML. AML with epithelial cysts, where the epithelial cyst has a cuboidal epithelial lining, account for the majority of them. Next, epithelioid AML (EAML) with cystic changes due to hemorrhage and necrosis, which is composed of epithelioid cells with abundant eosinophilic cytoplasm, have also been reported. These rare cystic types of AML can be mistaken for other cystic tumors, such as cystic renal cell carcinoma, in preoperative imaging. We report the imaging findings of a rare case of EAML with epithelial cysts.